Single-center Experience of Over a Hundred Implantations of a Transcutaneous Bone Conduction Device. Issue 9 (October 2017) - Dimitriadis, Panagiotis A.; Hind, Daniel; Wright, Kay; Proctor, Vicki; Greenwood, Larissa; Carrick, Suzanne; Ray, Jaydip
Abstract : Objective: To assess outcomes with a novel passive transcutaneous bone conduction device (t-BCD). Study Design: Prospective data collection and patient review. Setting: Tertiary referral center. Patients: Patients who underwent implantation with the t-BCD between November 2013 and September 2016. Intervention: Implantation of BAHA Attract. Main Outcome Measures: Surgical outcome, patient reported outcomes including the "Glasgow Benefit Inventory" and the "Client Oriented Scale of Improvement" for adults and the "Speech, Spatial and Qualities of Hearing scale" (SSQ-12) for children. Results: One hundred five patients were implanted. Numbness superior to the incision was commonly noticed. Four patients (3.8%) developed skin tenderness and redness that settled with conservative measures. Among those patients who had a conversion from a percutaneous Bone Conduction Hearing Device (BCHD) to the t-BCD (n=15), 1 (0.9%) developed seroma and 2 (1.9%) developed skin dehiscence at the edge of the implant magnet. Significant improvement in Client Oriented Scale of Improvement and Glasgow Benefit Inventory scores with a global satisfaction of 84% and 77.4% was observed for those previously aided and unaided respectively, with use of the device. A 22% improvement in SSQ-12 mean score was observed in the pediatric population. Conclusion: This is the largest single-center series reported on this t-BCD. The complication rate is small but caution is required in patients of conversion from a percutaneous BCHD. The patients' satisfaction is high and the need for aftercare is minimal. Cost-effectiveness evaluation of these devices, development of core outcome sets and well-designed, prospective trials to compare the different BCHDs should be the focus of future research.